2006
DOI: 10.1186/1471-2180-6-92
|View full text |Cite
|
Sign up to set email alerts
|

Use of CFSE staining of borreliae in studies on the interaction between borreliae and human neutrophils

Abstract: Background: Species of the tick-transmitted spirochete group Borrelia burgdorferi sensu lato (B. burgdorferi) cause Lyme borreliosis. Acute borrelial infection of the skin has unusual characteristics with only a mild local inflammatory response suggesting that the interaction between borreliae and the cells of the first-line defence might differ from that of other bacteria. It has been reported that human neutrophils phagocytose motile borreliae through an unconventional mechanism (tube phagocytosis) which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Previous work showed that macrophages, dendritic cells, and neutrophils can phagocytose and kill B. burgdorferi in vitro using conventional, coiling, or tube phagocytosis (9,(11)(12)(13)(14)(15)(16)(17)(18). Additional studies examined the in vivo role of neutrophils in controlling B. burgdorferi infection at the inoculation site and showed that increased neutrophil recruitment to the site of inoculation of engineered B. burgdorferi severely attenuates B. burgdorferi infectivity (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work showed that macrophages, dendritic cells, and neutrophils can phagocytose and kill B. burgdorferi in vitro using conventional, coiling, or tube phagocytosis (9,(11)(12)(13)(14)(15)(16)(17)(18). Additional studies examined the in vivo role of neutrophils in controlling B. burgdorferi infection at the inoculation site and showed that increased neutrophil recruitment to the site of inoculation of engineered B. burgdorferi severely attenuates B. burgdorferi infectivity (19).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that neutrophils have a limited role in controlling B. burgdorferi infection in mice in the conventional laboratory model system tested. Therefore, while macrophages, dendritic cells, and neutrophils have been shown to phagocytose B. burgdorferi in vitro using conventional, coiling, or tube phagocytosis (9,(11)(12)(13)(14)(15)(16)(17)(18), none of these innate immune effector cell types individually appears to have a major role in controlling B. burgdorferi infection in mice under conditions tested here or in our previous work (43). One caveat is that these cells types may have redundant phagocytic functions, so it is possible that one cell type can compensate for depletion of another in these experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether S. rugosus and S. rotundus are intracellular bacteria, we used carboxyfluorescein diacetate succinimidyl ester (CFSE; Invitrogen, Carlsbad, CA, USA) for staining of bacteria as previously described [14]. Briefly, 1×10 8 cells/ml of bacteria were washed once in phosphate buffered saline (PBS) and diluted in 500 µl of PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Erythromycin (5 g/ml) and tetracycline (2 g/ml) were added according to the selection requirements of the strains (47). Bacteria were washed once in phosphate-buffered saline (PBS) and stained with carboxyfluorescein succinimidyl ester (CFSE) (eBioscience) as described for flow cytometry (48). Briefly, bacteria in PBS were stained with CFSE at a final concentration of 5 M for 30 min at 37°C and protected from light.…”
Section: Methodsmentioning
confidence: 99%